4R Water Quality Impacts: An Assessment and Synthesis of Forty Years of Drainage Nitrogen Losses. Issue 6 (1st November 2015) - Christianson, L. E.; Harmel, R. D.
Abstract : The intersection of agricultural drainage and nutrient mobility in the environment has led to multiscale water quality concerns. This work reviewed and quantitatively analyzed nearly 1, 000 site‐years of subsurface tile drainage nitrogen (N) load data to develop a more comprehensive understanding of the impacts of 4R practices (application of the right source of nutrients, at the right rate and time, and in the right place) within drained landscapes across North America. Using drainage data newly compiled in the "Measured Annual Nutrient loads from AGricultural Environments" (MANAGE) database, relationships were developed across N application rates for nitrate N drainage loads and corn ( Zea mays L.) yields. The lack of significant differences between N application timing or application method was inconsistent with the current emphasis placed on application timing, in particular, as a water quality improvement strategy ( p = 0.934 and 0.916, respectively). Broad‐scale analyses such as this can help identify major trends for water quality, but accurate implementation of the 4R approach will require site‐specific knowledge to balance agronomic and environmental goals. Core Ideas: Analyzed nearly 1, 000 site‐years of cropping and drainage N load data. Neither N timing nor method treatments had significantly different drain N loads. Broad‐scale analyses such as this can help identify major trends for water quality.